SUPPLY CHAIN ANALYSIS OF SHALLOTS THROUGH RELATIONAL APPROACH (Study On Shallot Farmers in 4 District, East Java) - Wahyono, Agatha Christy; -, Kusdi; Worokinasih, Saparila (Accounting Department,, 2020)
ABSTRACTPurpose — This research aims to examine the effect of relational capital to supply chain integration and supply chain responsiveness.Design/methodology/approach — This research uses explanatory research with a quantitative approach. The object of this research was in four districts of East Java at Nganjuk, Kediri, Malang, and Probolinggo which are the centers of onion production that have similar environmental conditions. The sampling method in this research used multistage proportional random sampling with 200 respondents as a sample of this research. Data analysis uses the path analysis method by software SPSS 23.Findings — The results show that the relational capital has a positive and not significant effect on the supply chain integration and relational capital has a positive and significant effect on the supply chain responsiveness.Practical Implications — Supply chain responsiveness is greatly affected by the relational capital but not with the supply chain integration.Originality/value — Keywords Agroindustry, Relational Capital, Shallot, Supply Chain Integration, Supply Chain ResponsivenessPaper Type research paper (case study) Keyword: Agroindustry, Relational Capital, Shallot, Supply Chain Integration, Supply Chain Responsiveness